Coastal megacities: application of the driver-pressure-state-impact-response (DPSIR) framework to address environmental, social and economic issues - Sekovski, Ivan (2011)
Dissertação de mest., Gestão da Água e da Costa, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2010